Regional hydrothermal alteration and 18O-depletion of the ca. 620 Ma Huntington Mountain pluton and related rocks, Cape Breton Island, Canada - Petts, Duane; Longstaffe, Frederick; Potter, Joanna; Barr, Sandra; White, Chris (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2012)
ABSTRACT The ca. 620 Ma Huntington Mountain pluton and East Bay Hills Group, which comprise part of the Avalonian Mira terrane, Cape Breton Island, Nova Scotia, Canada, are characterized by pervasive propylitic alteration (chlorite, epidote, sericite, and Fe-Ti oxides) and low δ18O values (–3.8 to +6.2‰). This alteration is a product of interaction with hydrothermal fluids of meteoric and/or meteoric-seawater mixed origin at ~300 °C over a range of water/rock (w/r) ratios. Locally, the propylitic alteration was further overprinted by quartz-calcite-sericite alteration. Such samples have generally higher δ18OWR values (up to +9.5‰), reflecting interaction with evolved meteoric water at lower temperatures (~200 °C) and very low w/r ratios. The hydrothermal fluids responsible for widespread propylitic alteration of the Huntington Mountain-East Bay Hills complex (and regions beyond) likely entered the crust during initial rifting of the Mira terrane from Gondwana at ca. 575–550 Ma.